2018
DOI: 10.1038/s41467-018-06968-7
|View full text |Cite
|
Sign up to set email alerts
|

PRMT2 links histone H3R8 asymmetric dimethylation to oncogenic activation and tumorigenesis of glioblastoma

Abstract: Transcriptional deregulation has a vital role in glioblastoma multiforme (GBM). Thus, identification of epigenetic modifiers essential for oncogenic transcriptional programs is a key to designing effective therapeutics for this deadly disease. Here we report that Protein Arginine Methyltransferase 2 (PRMT2) is highly expressed in GBM and correlated with poor prognosis. The silencing or inactivation of PRMT2 inhibits GBM cell growth and glioblastoma stem cell self-renewal in vitro, and suppresses orthotopic tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 58 publications
0
68
0
Order By: Relevance
“…Thus, meArg has been associated with cancer progression and PRMTs have been considered as novel drug targets (68). In GBM, PRMT2 was shown to be overexpressed and is correlated with a poor prognosis (69). PRMT5 is also highly expressed in GBM, promotes self-renewal of GBM neurospheres (70), and resistance to mTOR inhibition in GBM cells lines and short-term patient cultures (71).…”
Section: Microautophagy In Glioblastomamentioning
confidence: 99%
“…Thus, meArg has been associated with cancer progression and PRMTs have been considered as novel drug targets (68). In GBM, PRMT2 was shown to be overexpressed and is correlated with a poor prognosis (69). PRMT5 is also highly expressed in GBM, promotes self-renewal of GBM neurospheres (70), and resistance to mTOR inhibition in GBM cells lines and short-term patient cultures (71).…”
Section: Microautophagy In Glioblastomamentioning
confidence: 99%
“…Additionally, enrichment of asymmetric dimethylation of H3R8 (H3R8me2a) is associated with known activating histone marks. This finding has implications in GBM tumorigenesis, in that, PRMT2 has been shown to act as a transcriptional co-activator of genes involved in oncogenesis and more specifically, GBM development [ 14 ]. Overexpression of PRMT2 in GBM pathogenesis makes it a potential target for tumor therapy but a potent small molecule inhibitor of PRMT2 has not yet been designed.…”
Section: Functional Significance Of Arginine Methylationmentioning
confidence: 99%
“…A variety of cancers have been linked to alterations in methyltransferase enzyme activity, including the brain tumors glioblastoma and medulloblastoma. Within the past decade, investigators have increasingly studied the role arginine methylation plays in brain tumors, particularly the relationship of PRMT activity to glioblastoma (GBM) and medulloblastoma development [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it was found that PRMTs have different catalytic sites and catalytic activities, and they are involved in the occurrence and development of a variety of cancers. The overexpression of PRMTs can promote cancer proliferation and metastasis [46][47][48]. For example, PRMT1, the most active member of the PRMTs family, can catalyze methylation of the FMS-like receptor tyrosine kinase 3internal tandem duplication protein at arginine 972/973.…”
Section: Prmts and Tumor Biological Characteristicsmentioning
confidence: 99%